Absence of the intestinal microbiota exacerbates hepatobiliary disease in a murine model of primary sclerosing cholangitis. Issue 1 (10th August 2015) - Tabibian, James H.; O'Hara, Steven P.; Trussoni, Christy E.; Tietz, Pamela S.; Splinter, Patrick L.; Mounajjed, Taofic; Hagey, Lee R.; LaRusso, Nicholas F.
Abstract : Primary sclerosing cholangitis (PSC) is a chronic, idiopathic, fibroinflammatory cholangiopathy. The role of the microbiota in PSC etiopathogenesis may be fundamentally important, yet remains obscure. We tested the hypothesis that germ‐free (GF) mutltidrug resistance 2 knockout (mdr2 −/− ) mice develop a distinct PSC phenotype, compared to conventionally housed (CV) mdr2 −/− mice. Mdr2 −/− mice (n = 12) were rederived as GF by embryo transfer, maintained in isolators, and sacrificed at 60 days in parallel with age‐matched CV mdr2 −/− mice. Serum biochemistries, gallbladder bile acids, and liver sections were examined. Histological findings were validated morphometrically, biochemically, and by immunofluorescence microscopy (IFM). Cholangiocyte senescence was assessed by p16 INK4a in situ hybridization in liver tissue and by senescence‐associated β‐galactosidase staining in a culture‐based model of insult‐induced senescence. Serum biochemistries, including alkaline phosphatase, aspartate aminotransferase, and bilirubin, were significantly higher in GF mdr2 −/− ( P < 0.01). Primary bile acids were similar, whereas secondary bile acids were absent, in GF mdr2 −/− mice. Fibrosis, ductular reaction, and ductopenia were significantly more severe histopathologically in GF mdr2 −/− mice ( P < 0.01) and were confirmed by hepatic morphometry, hydroxyproline assay, and IFM. Cholangiocyte senescence was significantly increased in GF mdr2 −/− mice and abrogated in vitro by ursodeoxycholic acid (UDCA) treatment. Conclusions : GF mdr2 −/− mice exhibit exacerbated biochemical and histological features of PSC and increased cholangiocyte senescence, a characteristic and potential mediator of progressive biliary disease. UDCA, a commensal microbial metabolite, abrogates senescence in vitro . These findings demonstrate the importance of the commensal microbiota and its metabolites in protecting against biliary injury and suggest avenues for future studies of biomarkers and therapeutic interventions in PSC. (Hepatology 2016;63:185–196)